Evaluation Of Accredited Social Health Activist’s Activities in Janani Suraksha Yojana in A Rural Area of Gwalior District, Madhya Pradesh - Mahore, Ram Niwas; Agarwal, Anil K; Kori, Sangeeta (National Journal of Community Medicine, 2015)
Background: ASHA is a health activist of Janani Suraksha Yojna under NRHM formulated to promote maternal and child health. This study was conducted with the purpose of evaluating knowledge, attitudes and practices of ASHA workers in relation to maternal & child health. Methodology: The study was conducted in a rural field practice area of G. R. Medical College, Gwalior using purposive sampling technique in 6 months duration. Active ASHAs working since at least 6 months and mothers delivered within last 6 months & giving breastfeeding to her child were included. Total 88 ASHAs were included. A pre-tested semi-structured questionnaire was designed for ASHA workers from their training module 2. Results: Antenatal registrations by ASHAs were 43%. ASHAs helped all the beneficiaries for JSY scheme registration. Eighty eight percent ASHAs were present with them at the time of delivery and ASHAs helped to 93 percent beneficiaries for getting JSY benefits to them. However in case of postnatal checkups only 33.33% ASHAs were found active. Level of knowledge and work performance was found in ASHAs respectively 50.85(±20.97) and 57.58(±18.90), that was statistically significant (<0.01) Conclusion: Observation of our study point towards better maternal and child health care in the area, which can be attributed to institutional delivery of pregnant mother related with significant monetary incentives.